Radiographical consolidation tumor size and preoperative clinical characteristics are significantly correlated with the postoperative survival of patients with part-solid and pure-solid adenocarcinomas: a propensity score-matched analysis - Hino, Haruaki; Maru, Natsumi; Utsumi, Takahiro; Matsui, Hiroshi; Taniguchi, Yohei; Saito, Tomohito; Kouda, Katsuyasu; Murakawa, Tomohiro (Surgery today (Tokyo, Japan), 2025)
Purpose Patients with part-solid adenocarcinomas treated by surgery generally have more favorable outcomes than those with pure-solid adenocarcinomas. We conducted this study to understand the effects of the lepidic components and preoperative characteristics on the postoperative survival of patients with part-solid adenocarcinomas. Methods The subjects of this retrospective study were 313 patients with stage 1 part-solid adenocarcinomas and 634 patients with pure-solid adenocarcinomas, treated at our institution between 2006 and 2020. Propensity score matching was performed to analyze survival in an unmatched cohort (PSM0, n = 313 vs. 634); a matched cohort based on the consolidation diameter (PSM1, n = 217 each); and a matched cohort based on 11 clinical characteristics (PSM2, n = 103 each). Multivariate analysis was also performed. Results The 5-year overall/recurrence-free survival rates for part-solid and pure-solid adenocarcinomas were 90.2%/79.3% and 80.8%/66.0% in the PSM0 cohort ( P < 0.0001), 87.4%/79.2% and 76.3%/68.6% in the PSM1 cohort ( P < 0.05), and 91.6%/92.1% and 76.6%/79.0% in the PSM2 cohort ( P > 0.05), respectively. Multivariate analysis revealed that male sex ( P = 0.04) and the carcinoembryonic antigen value ( P < 0.0001) were significant factors affecting overall survival, while the carcinoembryonic antigen value ( P = 0.0002) and consolidation tumor size ( P = 0.002) affected recurrence-free survival. The lepidic component was not related to overall ( P = 0.45) or recurrence-free ( P = 0.78) survival. Conclusions Preoperative factors are strongly associated with “consolidation size”, which could be the “representative factor” indicating the malignant potential in adenocarcinomas being consistent with the current eighth edition of the TNM.